A case study on the acoustical aspects and the best listening locality of experimental theatre University of Malaya / Chai Zhi-Jun - Chai , Zhi-Jun (2019)
Acoustics of a hall often overlook by most of the people or concert goer. There are many methods to measure the acoustics of a hall moreover many variables that will affect the result of it. Reverberation time of a hall is the most important aspect in acoustics context. However, music profession or non-music profession often value the hall in different way. This work focused on the listening position in Experimental Theatre, University of Malaya. By using six (6) different musical instruments that represent different musical families, the best listening position of each musical instrument in Experimental Theatre are found. Results from this experiment is compared with a survey that participated by music students in University of Malaya. This work is to provide a guideline for future improvement on the usage of Experimental Theatre. Frequency and loudness are used as the instrumentation to measure in the experiment. Results are presented in figures and tables form for better understanding. Questionnaire results are presented here in tables form.